2019
DOI: 10.1016/j.ijrobp.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Graduates' Job Preferences on the Current Radiation Oncology Job Market

Abstract: Purpose: To examine the role of radiation oncology (RO) graduates' application patterns and personal preferences in current labor concerns. Methods and Materials: An anonymous, voluntary survey was distributed to 665 domestic RO graduates from 2013 to 2017. Questions assessed graduates' regional (Northeast [NE]; Midwest [MW]; South [SO]; West [WT]) job type and population size preferences. Top regional choice was compared across other categorical and numerical variables using the χ 2 test and analysis of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The survey was sent to attending radiation oncologists practicing at our institution and was distributed to attending physicians who had graduated between 2013 and 2017 from Accreditation Council for Graduate Medical Education–accredited radiation oncology programs and had previously participated in a national radiation oncology survey. 3 The latter cohort was chosen because it represented a large population for whom email contacts were available.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was sent to attending radiation oncologists practicing at our institution and was distributed to attending physicians who had graduated between 2013 and 2017 from Accreditation Council for Graduate Medical Education–accredited radiation oncology programs and had previously participated in a national radiation oncology survey. 3 The latter cohort was chosen because it represented a large population for whom email contacts were available.…”
Section: Methodsmentioning
confidence: 99%
“…Anonymous survey results from graduated radiation oncology residents show that nearly two-thirds of graduates prefer jobs in large cities with regional jobs in the West and South sought after the most and least, respectively 6 . While the largest proportion of job vacancies were reported at urban practices (17.1%) compared to suburban (6.6%) and rural practices (8.3%), less than half of available jobs are located in large cities and a J o u r n a l P r e -p r o o f majority of job openings overall are located in the Midwest and South 3,4,6,7 . So at least part of the fear of oversupply may reflect perception rather than reality as job listings on the ASTRO Career Center website continue to show more listings than graduating residents 4,7 .…”
Section: Manuscriptmentioning
confidence: 99%
“…So at least part of the fear of oversupply may reflect perception rather than reality as job listings on the ASTRO Career Center website continue to show more listings than graduating residents 4,7 . Importantly, 75% of recent graduates received a job offer in their preferred geographical region 6 . On top of this, shifts away from private practices toward academic and satellite centers as well as changing compensation plans contribute to evolving job quality metrics within the field 3,4 .…”
Section: Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of recent graduates concluded that there exists a misalignment of geographic preferences (including regional preferences and city size) and job opportunities. 23 Although the American Society for Radiation Oncology recommends a board-certified radiation oncologist be present to supervise radiation therapy delivery in nearly all circumstances, less stringent CMS regulations have opened the door to the possibility of greater remote work for radiation oncologists, which could allow physicians to live closer to their desired locations while maintaining reasonable levels of patient access. Indeed, the impact of telemedicine is most likely to be evident in rural practices with marginal patient volumes; a single radiation oncologist could potentially oversee treatment for patients at multiple sites.…”
Section: Implications Of the “Virtual Radiation Oncology Clinic” Modementioning
confidence: 99%